Precutting round alfalfa and cornstalk bales decreases time and fuel required for bale breakup in a vertical mixer - Jones, S.Q.; Marston, T.T.; Kraus, R.M.; DeRouchey, Joel M.; Waggoner, Justin W.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Properly mixing and distributing nutrients throughout a ration can be equally as important as including them in the formulation. Many factors, including forage type, particle length, and mixer type, affect the homogeneity of total mixed rations. Particle size plays an important role in digestion and animal performance and, therefore, is an important consideration from harvest through feeding. An increase in particle size results in a less uniform distribution of nutrients throughout the total mixed ration. Typically, diets with a high proportion of forages have the lowest uniformity of nutrients in individual batches of complete feed.
Keywords: Beef; Alfalfa; Cornstalk bales; Vertical mixer